The Impact of Anthropomorphized Chatbot on Privacy Concern, Attitude Toward Advertisement, and Intention to Give Personal Information - Api Adyantari (MANAJEMEN DEWANTARA, 2022)
E-commerce developers add anthropomorphized chatbot features to their websites and application to assist customers in choosing the right product. The developers usually equipped them with many designs and elements, including the anthropomorphism element. Anthropomorphism attempts to immerse a non-human object with human aspects to give an impression of an actual human. However, using a chatbot does not always bring favorable outcomes. People might be afraid to interact with it since it resembles humans. This study aims to examine the weaknesses of an anthropomorphized chatbot further. After interacting with a chatbot, people’s responses, such as their privacy concern, attitude toward advertisements from the chatbot, and their intention to disclose personal information, were investigated in this study. A Questionnaire was developed to collect the data in this study. The respondents were recruited from Amazon MTurk. 222 responses were collected for this study. All hypotheses were analyzed using SPSS and SmartPLS statistical tools. The result showed that anthropomorphism elements in chatbots positively affect people’s privacy concerns. Privacy concern negatively affects people’s attitude toward advertisement from chatbots and their intention to disclose personal information.